Force-bearing phagocytic adhesion rings mediate the phagocytosis of surface-bound particles - Subhankar Kundu; Kaushik Pal; Arghajit Pyne; Xuefeng Wang (Nature Communications)
Abstract Many micro-particles including pathogens strongly adhere to hosts. It remains elusive how macrophages detach these surface-bound particles during phagocytosis. We show that, rather than binding directly to these particles, macrophages form unique β2 integrin-mediated adhesion structures at the cell-substrate interfaces, specifically encircling the surface-bound particles. These circular adhesion structures that we named phagocytic adhesion rings (PARs) serve as strongholds to support local ring-shaped actin structures constricting into the particle-substrate cleavages, thereby pinching off the particles from the substrate. During this process, integrins in PARs sustain tensions due to the reaction force of actin polymerization against the particles. Such tensions are critical for phagocytic efficiency of surface-bound particles. PARs were formed in all tested macrophages (mouse, human and fish) and micron-sized particles (microbeads and E. coli), demonstrating their conserved role in the phagocytosis. This study reveals a mechanism of PAR-mediated phagocytosis, specialized for the detachment and internalization of surface-bound particles.